Cadmium Content of South African Table Wines - Zeeman, W.; Du Plessis, C. S. (South African Journal of Enology and Viticulture, 2017)
Red and white South African table wines from the major wine producing districts were analysed for cadmium content. Only three wines had a slightly higher concentration than 0,010 mg/ t The average cadmium concentration was 0,003 mg/ f, and no relationship between cadmium content and origin could be determined.